Tarcza Prywatności UE–USA po kolizji w „bezpiecznej przystani”. Zakres ochrony prywatności po wyroku w sprawie C-362/14 Schrems - Majkowska-Szulc, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Transfer of personal data is an essential element of the transatlantic trade relationship, because the EU and the United States are for each other the most important trading partners. Data transfers increasingly form an integral part of their commercial exchanges. The Court of Justice of the European Union ruling of 6 October 2015 in case C-362/14 Schrems reaffirmed the importance of the fundamental right to the protection of personal data, as enshrined in the Charter of Fundamental Rights of the EU, including the situation when such data are transferred outside the EU. In the wake of the hereinabove judgement the transatlantic data transfer has been regulated anew. European Commission has launched EU-U.S. Privacy Shield in order to ensure stronger protection for transatlantic data flows. This article aims to analyse the importance and results of the above-mentioned judgement.
Keywords: Privacy Shield; European Union; USA; privacy protection; Schrems Case